PD-1 blockade reverses adaptive immune resistance induced by high-dose hypofractionated but not low-dose daily fractionated radiation - Morisada, Megan (Oncoimmunology, 2017)
Preclinical evidence suggests that high-dose hypofractionated ionizing radiation (IR) can enhance anti-tumor immunity and result in significant tumor control when combined with immune checkpoint blockade (ICB). However, low-dose daily fractioned IR used for many tumor types including head and neck squamous cell carcinoma results in lymphopenia and may be immunosuppressive. We compared immune correlates, primary tumor and abscopal tumor control rates following the addition of PD-1 mAb to either high-dose hypofractioned (8Gyx2) or low-dose daily fractionated (2Gyx10) IR in syngeneic models of cancer. When compared to 2Gyx10 IR, 8Gyx2 IR preserved peripheral and tumor-infiltrating CD8(+) T-lymphocyte accumulation and activation and reduced peripheral and tumor gMDSC accumulation. Regulatory T-lymphocytes were largely unaltered. Type I and I IFN levels and expression of IFN-responsive MHC class I and PD-L1 was enhanced in tumors treated with 8Gyx2 compared to 2Gyx10 IR. Functionally, tumor-specific CD8(+) T-lymphocyte IFN responses within tumor draining lymph nodes were enhanced following 8Gyx2 IR but suppressed following 2Gyx10 IR. When combined with PD-1 mAb, reversal of adaptive immune resistance and subsequent enhancement of CD8+ cell dependent primary and abscopal tumor control was observed following 8Gyx2 but not 2Gyx10 IR. These data strongly support that compared to daily fractionated low-dose IR, high-dose hypofractionated IR preserves or enhances anti-tumor immunity and, when combined with PD-1 mAb to reverse adaptive immune resistance, promotes anti-tumor immunity to control primary and distant tumors. These data critically inform the rational design of trials combining IR and ICB.